Parque Interactivo-Industrial natural y cultural La Siberia en la Antigua Fabrica de Cementos Samper del Municipio de La Calera (2021)
The Cement Factory La Siberia located in the municipality of La Calera, was of great importance for the history and development of Colombia, especially for the growth of Bogota, for being one of the first cement factories in the country, however, given its abandonment and disuse for more than 20 years, it is currently in a state of deterioration and oblivion. With the main objective of valuing, reusing and recycling the architecture of an Industrial Heritage property, the Natural and Cultural Industrial-Interactive Park La Siberia was created. The new proposed use focuses on the balance between the solution of the historical, environmental and social problems of the sector, and the articulation of the Municipality of La Calera and the Chingaza Natural Park through a heritage landmark by means of a proposal for a sustainable activity, learning and fun, from the implementation of an interactive infrastructure and the development of an Industrial Park that socially and economically benefits the inhabitants of the municipality.